2014
DOI: 10.1371/journal.pone.0115581
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Root Exudates from the Hyperaccumulator Sedum alfredii under Cadmium Stress: Metabonomics Analysis

Abstract: Hydroponic experiments were conducted to investigate the variation of root exudates from the hyperaccumulator Sedum alfredii under the stress of cadmium (Cd). S. alfredii was cultured for 4 days in the nutrient solution spiked with CdCl2 at concentrations of 0, 5, 10, 40, and 400 µM Cd after the pre-culture. The root exudates were collected and analyzed by GC-MS, and 62 compounds were identified. Of these compounds, the orthogonal partial least-squares discrimination analysis (OPLS-DA) showed that there were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…For example, an Arabidopsis ABC transporter mutant caused significant changes to the natural microbial community compared to the wild type (40), and these differences in root exudation supported distinct rhizosphere bacterial communities (41). The mechanisms underlying the occurrence of different bacterial communities in the rhizospheric zones of HE and NHE under Cd stress requires further investigation, though differences of the exudate profile between the two S. alfredii ecotypes have been reported (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an Arabidopsis ABC transporter mutant caused significant changes to the natural microbial community compared to the wild type (40), and these differences in root exudation supported distinct rhizosphere bacterial communities (41). The mechanisms underlying the occurrence of different bacterial communities in the rhizospheric zones of HE and NHE under Cd stress requires further investigation, though differences of the exudate profile between the two S. alfredii ecotypes have been reported (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Metals present in the rhizosphere of hyperaccumulators are more bioavailable than those in the rhizosphere of non hyperaccumulators [105][106][107]. However, root exudates produced by the Cd and Zn hyperaccumulator Thlaspi caerulescens did not signifi cantly increase metal mobility [101,108].…”
Section: Plant Characteristicsmentioning
confidence: 99%
“…Organic acids represent the dominant moiety in the root exudates, particularly, in relation to metal solubilization in the rhizosphere region (Chiang et al 2011;Luo et al 2014). Kim et al (2010) reported that oxalic and citric acids secreted by Echinochloa crusgalli significantly increased the micronutrient uptake and translocation in plant tissues.…”
Section: Organic Acid Secretion and Proton Extrusionmentioning
confidence: 99%